Effect of Forest Covers on Physico-chemical Properties of Soils Developed on Sand Stone - Totey, N. G.; Singh, A. K.; Bhowmik, A. K.; Khatri, P. K. (Indian Forester, 1986)
Physico-chemical properties of soils belonging to great group of Haplustali/Hapiustoli and developed from Gondwana land stone in similar physiographic and environmental conditions were studied under three forest covers Viz., miscellaneous cover, teak plantation and Eucalyptus cover in Kotma and Ghunghuti ranges of South Shahdol and North Shahdol Divisionl of M.P. respectively. Weathering processes seem to be quite active in soils under followed by Eucalyptus cover. Ratios of clay to non clay fractionl, thickness of 'A' horizon, per cent organic matter, cation exchange capacity, exchangeable Ca and Mg were more under teak cover than that of Eucalyptus. Soil pH lowered down more under Eucalyptus plantation than in teak plantation. Soluble salts were more under Eucalytus cover. Performance of Eucalyptus was better on Ghunghuti range where as teak was better on Kotma rangue Eucalyptus supports undergrowth of different tree species.